Does pre-COVID impulsive behaviour predict adherence to hygiene and social distancing measures in youths following the COVID-19 pandemic onset? Evidence from a South African longitudinal study. - Katharina Haag; Stefani Du Toit; Nace Mikus; Sarah Skeen; Kathryn Steventon Roberts; Marguerite Marlow; Vuyolwethu Notholi; Akhona Sambudla; Yeukai Chideya; Lorraine Sherr; Mark Tomlinson (BMC, 2023)
Abstract Background Engagement in protective behaviours relating to the COVID-19 pandemic has been proposed to be key to infection control. This is particularly the case for youths as key drivers of infections. A range of factors influencing adherence have been identified, including impulsivity and risk taking. We assessed the association between pre-COVID impulsivity levels and engagement in preventative measures during the COVID-19 pandemic in a longitudinal South African sample, in order to inform future pandemic planning. Methods Data were collected from N = 214 youths (mean age at baseline: M = 17.81 (SD = .71), 55.6% female) living in a South African peri-urban settlement characterised by high poverty and deprivation. Baseline assessments were taken in 2018/19 and the COVID follow-up was conducted in June-October 2020 via remote data collection. Impulsivity was assessed using the Balloon Analogue Task (BART), while hygiene and social distancing behaviours were captured through self-report. Stepwise hierarchical regression analyses were performed to estimate effects of impulsivity on measure adherence. Results Self-rated engagement in hygiene behaviours was high (67.1-86.1% "most of the time", except for "coughing/sneezing into one's elbow" at 33.3%), while engagement in social distancing behaviours varied (22.4-57.8% "most of the time"). Higher impulsivity predicted lower levels of hygiene (β = .14, p = .041) but not social distancing behaviours (β = −.02, p = .82). This association was retained when controlling for a range of demographic and COVID-related factors (β = .14, p = .047) and was slightly reduced when including the effects of a life-skills interventions on hygiene behaviour (β = −.13, p = .073). Conclusions Our data indicate that impulsivity may predict adolescent engagement in hygiene behaviours post COVID-19 pandemic onset in a high risk, sub-Saharan African setting, albeit with a small effect size. For future pandemics, it is important to understand predictors of engagement, particularly in the context of adversity, where adherence may be challenging. Limitations include a small sample size and potential measure shortcomings.